DETERMINAN MINAT PENGGUNAAN E-SPT - Ramadani, Marta; Lutfillah, Novrida Qudsi (Widya Mandala Surabaya Catholic University, 2020)
This study aims to examine and analyze the influence of perceptions of usability, trust and computer self efficacy on the interest in using e-SPT in Surabaya. Respondents in this study were 90. Samples were taken using quota sampling with non probability sampling techniques.Data analysis was performed using statistics with SPSS tools. Based on the results of data analysis using the t test it is known that partially the perception of usability, trust and computer self efficacy has a positive and significant influence on the interest in using e-SPT. While based on the results of data analysis using the F test it is known that simultaneously the perception of usability, trust and computer self efficacy has a positive and significant effect on the interest in using e-SPT.